Retrofit measures evaluation considering thermal comfort using building energy simulation : two Lisbon households - Gomes, Ricardo (2019)
ABSTRACT: Retrofit measures for buildings are in general evaluated considering the energy savings and life cycle cost. However, one of the main benefits, the increase of users comfort is very seldom analysed. In this work, two residential households representative of a large share of households in Portugal, were monitored and its thermal behavior was modeled using Energy Plus. The thermal evaluation of the pre-retrofit households shows that the winter season is problematic due to construction solutions and low availability for heating. The retrofit measures analysis was performed considering different retrofit solutions regarding envelope improvement and efficient systems implementation. In order to work around the question of comparing households that do not use energy for acclimatization and therefore have very low energy consumption, in the retrofit scenarios it was considered the thermal comfort evaluation value for the real case (pre-retrofit) and compared the energy consumption to achieve that same average comfort level (in this case avoiding high discomfort peaks). The measures that more rapidly pay the investment are those related with implementing active systems. The approach used in this paper, should be used in more calibrated models in order to have overall conclusions about the retrofit process at a larger scale.